Mako - Ynion, Jan Karlo Carandang 1993- (Quezon City College of Mass Communication, University of the Philippines Diliman, 2016)
"Mako is a happy-go-lucky boy in his last year as high school student. Everyday, he exerts so much effort to make his hair stand out or at least be at par with his classmates. When he starts losing his hair, his world turned up side down and decides not to go to school anymore. But when he started to get closer to his friends, he starts to feel the confidence he needs for his journey to self-acceptance. According to Cognitive Dissonance Theory, when one experiences a disconnect between behavior and attitudes, cognitive dissonance theory predicts that he is then highly motivated to restore a sense of equilibrium. The framework guides the character's behavioral change toward his self-perception. The character focuses on the positive attributes of being bald to improve his self-esteem."
Vita.
Undergraduate thesis
Keywords: Mako (Short film) -- Philippines; Short films -- Philippines